PENGARUH PENDAPATAN ANGGOTA TERHADAP TINGKAT SIMPANAN PADA CU LANTANG TIPO TP JERUJU PONTIANAK - Ignasius Minggus; Parijo Parijo; F.Y. Khosmas (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
Abstrack This thesis is titled "The Influence of Member Income Against the Level of Deposits in CU Lantang Tipo TP Jeruju Pontianak. In this thesis is motivated by the income of members in CU Lantang Tipo TP Jeruju Pontianak, has a habit of doing savings. The research method used in this study is a quantitative research approach. Analysis of the data used in this study is to use a simple linear regression analysis technique, Y = a + bX. The results of this study are: (1) there is an influence of income on member savings in CU Lantang Tipo TP Jeruju Pontianak, this can be seen from the results of the t test analysis proven t count (income) of 18,118> t table1,661, then Ha is accepted and Ho rejected. In other words reject the null hypothesis (Ho) and accept the alternative hypothesis (Ha). The results of this study can be concluded that there is an influence of income on member savings in CU Lantang Tipo TP Jeruju Pontianak. The influence of income on member savings in CU Loud Tipo TP Jeruju Pontianak is 77.9%, this can be seen from the results of the determinant coefficient test, the r count is known to be 0.883 so then to find out how much influence the variable X has on the variable Y using the determinant coefficient r2 with using the formula R2 = r2 x 100%. From the calculation results obtained 77.9%. So it can be concluded that there is an effect of variable X on Y by 77.9%. This means that there is an effect of income on member savings of 77.9% and of which 22.1% is another factor not examined by researchers.Keywords: Member Revenue. Deposit on CU Lantang Tipo TP Jeruju Pontianak